Selection and Characterization of Human Immunodeficiency Virus Type 1 Variants Resistant to the (+) and (−) Enantiomers of 2′-Deoxy-3′-Oxa-4′-Thio-5-Fluorocytidine - Richard, Nathalie (American Society for Microbiology, 2000)
Human immunodeficiency virus (HIV) type 1 (HIV-1) variants were selected for resistance to the (+) and (−) enantiomers of a novel nucleoside analogue, 2′-deoxy-3′-oxa-4′-thio-5-fluorocytidine (dOTFC), by use of the infectious molecular clone HIV HXB2D and the human T-cell line MT-4. The dOTFC-resistant variants that were selected were 10-fold less sensitive than wild-type virus, and cloning and sequencing of the complete reverse transcriptase (RT)-coding region identified the mutation M184V. Studies with mutated recombinant HXB2D virus confirmed the importance of the M184V mutation in conferring resistance to (−)dOTFC in MT-4 cells, although no difference in sensitivity was observed in primary cells. The M184V substitution also displayed decreased susceptibility to (+)dOTFC. Selection with (+)dOTFC also produced variants which were 10-fold more resistant than the wild type, and a novel mutation, D67G, was identified following cloning and sequencing of the RT genes. The D67G mutation was introduced into HXB2D by site-directed mutagenesis, and the data obtained confirmed the importance of this mutation in conferring resistance to both (+)dOTFC and (−)dOTFC. Mutated recombinant molecular clone HXB2D-D67G was further selected with (+)dOTFC, and three of six clones sequenced contained both the D67G and M184V mutations, while the other three of the six clones contained only the D67G mutation. Clinical isolates of HIV-1 which are (−) 2′-deoxy-3′-thiacytidine-resistant also displayed resistance to both (+)dOTFC and (−)dOTFC.